Pengaruh Penambahan Kotoran Ternak sebagai Bioaktivator pada Pengomposan Eceng Gondok dan Limbah Pisang dengan Metode Takakura - Arifin, Arifin; Yudhiantoro, Galih Dwi; Sulastri, Aini (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
Punggur Kecil is a village in Sungai Kakap District whose residents live in the agricultural and plantation sectors. Harvested banana waste and hyacinth can be used as compost. This area has a large livestock population, so the amount of livestock manure produced is also large. Livestock manure can be used as organic fertiliser. This research aims to identify the physical and chemical parameters of compost produced based on Minister of Agriculture Decree Number 261 of 2019 and to analyse the effect of bioactivators from livestock manure on compost quality. The method used is Takakura for making compost and Organoleptic Test for physical tests. The research showed that the control (K0) was odourless, blackish brown, and had a rough texture. Cow compost (K1) smells bad, is black, and has a rough texture. Goat compost (K2) is odourless, blackish, and has a rough texture. Chicken compost (K3) is odourless, blackish, and has a rough texture. The water content parameters K0, K1, K2, and K3 have a value of 88.53%; 86.04%; 82.79%; and 78.8%, C-organic value of 44.47%; 45.18%; 42.66%; and 29.53%, and NPK of 4.93%; 5.42%; 5.47%; and 7.50%. In addition, the use of bioactivators can affect chemical and physical parameters.